(3GdacQ GdGSJQGJjLj (B:s (3bQGAGJ eYGUQI (B/s - (3GdNaGLj, fYeI YHGSs; (3GdLHhQj YHO GdQMeGfs; (3eMSf, GdZGdHj WGgQ s ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ h GdJhRjY(B, s, 2008)
(3jJVef gPG GdcJGH eGjdj (B: (3efWb EOGQI GdJMOjGJ GdESJQGJjLjI aj efXeGJ GdCYeGd (B-(3JMdjd GdOhQ GdESJQGJjLj dJcfhdhLjG GdeYdheGJ aj efXeGJ GdCYeGd (B-(3efWb GdEOGQI GdESJQGJjLjI GdCYeGd GdGdcJQhfjI hab GdeOQSI GdeYQajI (B-(3JMdjd JCKjQ JcfhdhLjG GdeYdheGJ aj GdebOQGJ GdLhgQjI(B((3OQGSI ejOGfjI(B) -(3edGeM fThA GdacQ GdESJQGJjLj heOGNd gfOSJg (B-(3edGeM GdTNUjI GdESJQGJjLjI ddeOQjjf(B((3efXhQ eYQaj(B)(3JMdjd OhQ GdbjGOI GdESJQGJjLjI aj efXeGJ GdCYeGd (B-(3GdJMdjd GdeYQaj ddJUhQ hGdJhLg hGdJacjQ GdESJQGJjLj (B-(3QCS GdeGd GdESJQGJjLj(B((3acQI hedGeM(B) -(3GdJUhQ GdeYQaj hGdCNdGbj ddbhI GdESJQGJjLjI defXeGJ GdCYeGd (B-(3YbdGfjI GdJMGdaGJ GdESJQGJjLjI(B((3GdhaQGJ hGdcda(B) -(3JMdjd GdeMaXI GdESJQGJjLjI hab GdeONd GdeYQaj(B((3JCWjQ fXQj(B)s
(3HjHdjhZQGajG U(B.327s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdeTQhYGJs; (3GdJNWjWs; (3GdKbGaIs; (3GdacQs; (3GdeYdheGJ GdEOGQjIs